Exposure to the environmentally toxic pesticide maneb induces Parkinson's disease-like neurotoxicity in mice: A combined proteomic and metabolomic analysis. (December 2022) - Liu, Chaoyang; Liu, Zehua; Fang, Yanyan; Du, Zhen; Yan, Zhi; Yuan, Xin; Dai, Lijun; Yu, Ting; Xiong, Min; Tian, Ye; Li, Honghu; Li, Fei; et al.
Abstract: Maneb is a typical dithiocarbamate fungicide that has been extensively used worldwide. Epidemiological evidence shows that exposure to maneb is an environmental risk factor for Parkinson's disease (PD). However, the mechanisms underlying maneb-induced neurotoxicity have yet to be elucidated. In this study, we exposed SH-SY5Y cells to maneb at environmentally relevant concentrations (0, 0.1, 5, 10 mg/L) and found that maneb dose-dependently decreased the cell viability. Furthermore, maneb (60 mg/kg) induced PD-like motor impairment in α-synuclein A53T transgenic mice. The results of tandem mass tag (TMT) proteomics and metabolomics studies of mouse brain and serum revealed significant changes in proteins and metabolites in the pathways involved in the neurotransmitter system. The omics results were verified by targeted metabolomics and Western blot analysis, which demonstrated that maneb induced disturbance of the PD-related pathways, including the phenylalanine and tryptophan metabolism pathways, dopaminergic synapse, synaptic vesicle cycle, mitochondrial dysfunction, and oxidative stress. In addition, the PD-like phenotype induced by maneb was attenuated by the asparagine endopeptidase (AEP) inhibitor compound #11 (CP11) (10 mg/kg), indicating that AEP may play a role in maneb-induced neurotoxicity. To the best of our knowledge, this is the first study to investigate the molecular mechanisms underlying maneb-induced PD-like phenotypes using multiomics analysis, which identified novel therapeutic targets for PD associated with pesticides and other environmental pollutants. Graphical abstract: Image 1 Highlights: Maneb disturbs neurotransmitter biosynthesis and neurotransmitter signaling. Maneb impairs dopaminergic neurons through mitochondrial dysfunction and oxidative stress. AEP inhibitor compound #11 protects against the toxic effect of maneb in mice.